Synthesis and Molecular Modeling of Some Novel Hexahydroindazole Derivatives as Potent Monoamine Oxidase Inhibitors - Gökhan-Kelekçi, N.; Şimşek, O.O.; Ercan, A.; Yelekçi, K.; Şahin, Z.S.; Işík, S.; Uçar, G. (Pergamon-Elsevier Science Ltd, 2009)
A novel series of 2-thiocarbamoyl-2,3,4,5,6,7-hexahydro-1H-indazole and 2-substituted thiocarbamoyl-3,3a,4,5,6,7-hexahydro-2H-indazoles derivatives were synthesized and investigated for the ability to inhibit the activity of the A and B isoforms of monoamine oxidase (MAO). The target molecules were identified on the basis of satisfactory analytical and spectra data (IR, 1H NMR, 13C NMR, 2D NMR, DEPT, EI-MASS techniques and elemental analysis). Synthesized compounds showed high activity against both the MAO-A (compounds 1d, 1e, 2c, 2d, 2e) and the MAO-B (compounds 1a, 1b, 1c, 2a, 2b) isoforms. In the discussion of the results, the influence of the structure on the biological activity of the prepared compounds was delineated. It was suggested that non-substituted and N-methyl/ethyl bearing compounds (except 2c) increased the inhibitory effect and selectivity toward MAO-B. The rest of the compounds, carrying N-allyl and N-phenyl, appeared to select the MAO-A isoform. The inhibition profile was found to be competitive and reversible for all compounds. A series of experimentally tested (1a-2e) compounds was docked computationally to the active site of the MAO-A and MAO-B isoenzyme. The autodock 4.01 program was employed to perform automated molecular docking. In order to see the detailed interactions of the docked poses of the model inhibitors compounds 1a, 1d, 1e and 2e were chosen because of their ability to reversibly inhibit the MAO-B and MAO-A and the availability of experimental inhibition data. The differences in the intermolecular hydrophobic and H-bonding of ligands to the active site of each MAO isoform were correlated to their biological data. Observation of the docked positions of these ligands revealed interactions with many residues previously reported to have an effect on the inhibition of the enzyme. Excellent to good correlations between the calculated and experimental Ki values were obtained. In the docking of the MAO-A complex, the trans configuration of compound 1e made various very close interactions with the residues lining the active site cavity these interactions were much better than those of the other compounds tested in this study. This tight binding observation may be responsible for the nanomolar inhibition of form of MAOA. However, it binds slightly weaker (experimental Ki = 1.23 μM) to MAO-B than to MAO-A (experimental Ki = 4.22 nM). © 2009 Elsevier Ltd. All rights reserved.
Keywords: Docking; Hexahydroindazole; MAO-A/MAO-B Inhibition; X-Ray Crystallographic Model